2010
DOI: 10.3727/096368910x314161
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Human Erythroid Output in NOD/SCID Mice Reconstituted with Human Hematopoietic Stem Cells

Abstract: The third-generation NOD/LtSz-scid/IL2Rγnull (NOD/SCID IL2Rγnull) mouse represents a significantly improved xenograft model allowing high levels of human leukocyte engraftment over extended follow up. One remaining limitation of this mouse model, however, is the low level of circulating human erythrocytes. We established a practical ex vivo erythroid culture system of xenograft marrow progenitors to enrich for human erythroid progeny. At various time points after transplant, erythroid cells were easily assayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
2
12
1
1
Order By: Relevance
“…This suggests that hiPSC-derived erythropoiesis mimics that of human development and recapitulates accordingly the globin gene switch. It also indicates that complete maturation of immature erythroid cells can take place under the influence of an adult hematopoietic microenvironment, as we have already described for cord blood cells, 30 and in accordance with observations of Hayakawa et al 32 that the combination of the murine marrow microenvironment and cytokines is sufficiently potent to mimic the normal post-natal human hemoglobin switching process. We assume that the delay required for the cells to achieve complete hemoglobin switching is linked to their stage of maturation.…”
Section: Discussionsupporting
confidence: 63%
“…This suggests that hiPSC-derived erythropoiesis mimics that of human development and recapitulates accordingly the globin gene switch. It also indicates that complete maturation of immature erythroid cells can take place under the influence of an adult hematopoietic microenvironment, as we have already described for cord blood cells, 30 and in accordance with observations of Hayakawa et al 32 that the combination of the murine marrow microenvironment and cytokines is sufficiently potent to mimic the normal post-natal human hemoglobin switching process. We assume that the delay required for the cells to achieve complete hemoglobin switching is linked to their stage of maturation.…”
Section: Discussionsupporting
confidence: 63%
“…24 The failure of human cytokine treatment to improve human RBC reconstitution in humanized mice without macrophage depletion further supports the argument that macrophages pose a critical obstacle to human RBC reconstitution in humanized mice.…”
Section: Org Frommentioning
confidence: 76%
“…on May 10, 2018. by guest www.bloodjournal.org From This is consistent with a recent study showing that bone marrow recovered from humanized mice could differentiate into human erythroid cells ex vivo. 24 The failure of human cytokine treatment to improve human RBC reconstitution in humanized mice without macrophage depletion further supports the argument that macrophages pose a critical obstacle to human RBC reconstitution in humanized mice.…”
mentioning
confidence: 76%
“…We successfully achieved stable, long-term expression of the transduced GFP gene that was most robust in cells transfected with constructs containing cellular polypeptide chain EF1α and human cytomegalovirus (CMV) promoter [85]. A novel and interesting approach by Hayakawa et al demonstrated the feasibility of long-standing, viral introduced GFP expression in CB CD34 + cells under in vivo condition [86]. Three months after injecting GFP transduced, human CB CD34 + cells into nonobese diabetic/severe combined immunodeficient NOD/SCID IL2R γ null mouse, a significant (33%) percentage of peripheral blood cells were positive for the human CD45 marker, out of which 79.4% were GFP positive.…”
Section: Cb Epcs In Optical Imagingmentioning
confidence: 99%
“…Three months after injecting GFP transduced, human CB CD34 + cells into nonobese diabetic/severe combined immunodeficient NOD/SCID IL2R γ null mouse, a significant (33%) percentage of peripheral blood cells were positive for the human CD45 marker, out of which 79.4% were GFP positive. In addition, cells harvested from the bone marrow of mice that received GFP + CB CD34 + cells exhibited GFP expression in ex vivo culture for up to 18 days post-plating [86]. Despite the efforts to optimize and improve techniques based on introducing and stably maintain GFP expression in transduced cells, drawbacks related to GFP detection and imaging still exist.…”
Section: Cb Epcs In Optical Imagingmentioning
confidence: 99%